PROGRAM KERJA DIKLATSAR DALAM MENINGKATKAN KEMAMPUAN BERMAIN MUSIK SABDA KINNARA UNNES MARCHING BAND (Universitas Negeri Semarang, 2016)
The last few years in Semarang emergence a phenomenon of marching band unit raging from community organizations, universities and school environment, so that the unit of the newly established marching band can manage their unit. This study aims to: (1) knowing the purpose, methods and materials Diklatsar SKUMB; (2) Determine the ability to play music SKUMB members after attending basic training. The method used is a qualitative method, so this is a descriptive study that provides an overview as carefully as possible about matters under investigation. Data collection techniques in this study using observation, interview and documentation. Technique authenticity of data is done by triangulation techniques, and data analysis conducted in stages, data reduction, data presentation and conclusion or verification. The results showed that (1) Interest Diklatsar SKUMB is Increasing levels of experience and knowledge of students about the marching band; Improving student knowledge about management and the implementation of UKM’s; Improving the quality of work of the marching band; Improving leadership for participants of activities. (2) Educational materials basic training SKUMB includes elements of appearance (display and charts) as well as the skills of playing music (rhythm, melody, and harmony; (3) Ability to play music member SKUMB after attending basic training is successfully playing songs training materials in which includes the ability plays rhythm, melody and harmony.